PENGARUH PENGGUNA MEDIA SOSIAL TERHADAP PENINGKATAN PENJUALAN UMKM DESA: (Studi Kasus Desa Demung) - Ahadiyah, Kurnia; Ridwan, Ahmad (Proceedings of Annual Conference on Community Engagement, 2024)
This research aims to find out the influence of the intensity of social media use on increasing UMKM sales in Demung Village, Besuki District, Situbondo Regency. By using the Partial T Test, the research results show that there is a significant influence between the use of WhatsApp social media on the sales results of UMKM products. Meanwhile, the use of social media such as Instagram, Facebook and TikTok is still not being utilized properly. This is indicated by the significance value of each variable still being more than 0.05. Only the WhatsApp variable has a significance value of less than 0.05. Product sales results also experienced significant differences between before they were marketed using social media and after using social media.